Roles of AMPK in energy homeostasis and nutrient sensing - Hardie, Grahame (Henry Stewart Talks, 2021)
AMPK as an energy sensor, Canonical activation of AMPK, Structure of AMPK, Non-canonical activation of AMPK, A drug target in type 2 diabetes, A drug target in cancer